2018
DOI: 10.1001/jamadermatol.2017.5795
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Follicular and Epidermal Cell Suspension as a Novel Surgical Approach in Difficult-to-Treat Vitiligo

Abstract: IMPORTANCE Epidermal cell suspension (ECS) and follicular cell suspension (FCS) are successful surgical modalities for the treatment of stable vitiligo. However, repigmentation in generalized and acrofacial vitiligo and over acral or bony sites (eg, elbows, knees, iliac crests, and malleoli), which are difficult to treat, is challenging. OBJECTIVE To study the efficacy of transplanting a combination of autologous, noncultured ECS and FCS (ECS + FCS) compared with ECS alone in stable vitiligo. DESIGN, SETTING, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 37 publications
4
39
0
Order By: Relevance
“…The overall reported efficacy of NB‐UVB phototherapy in attaining >75% repigmentation ranged from 12.5% to 75%, that too after a period of 1 year . The similar outcome can be achieved within 4 months by NCES as per the published clinical trials . Hence, NCES is an efficacious alternative to phototherapy in stable vitiligo.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The overall reported efficacy of NB‐UVB phototherapy in attaining >75% repigmentation ranged from 12.5% to 75%, that too after a period of 1 year . The similar outcome can be achieved within 4 months by NCES as per the published clinical trials . Hence, NCES is an efficacious alternative to phototherapy in stable vitiligo.…”
Section: Discussionmentioning
confidence: 69%
“…have demonstrated improvement of repigmentation outcome by suspending the melanocytes in the patients’ own serum. Razmi et al . have shown that the addition of non‐cultured hair follicular cell suspension into the NCES improves its repigmentation outcome, even in difficult‐to‐treat vitiligo.…”
Section: Discussionmentioning
confidence: 99%
“…A transparent sheet affords reliable measurement of lesion size (Aydin et al., ); however, it is difficult to assess the extent of perifollicular repigmentation after treatment. Digital image analysis systems accurately measure lesion size (van Geel, Vander Haeghen, Ongenae, & Naeyaert, ; Lommerts et al., ; Razmi et al., ), but require a set of pre‐ and post‐treatment photographs of the same size and angle of incidence, which is not always available. A quartile method based on a rough estimate has often been used to evaluate the treatment response (Bae, Yoo, Kim, Lee, & Kim, ; Passeron et al., ; Silpa‐Archa et al., ), but this approach has never been validated and is somewhat arbitrary.…”
Section: Introductionmentioning
confidence: 99%
“…Further comparative studies on FCS have reinforced the impression of inferior results obtaining with FCS, questioning the added advantage of melanocyte precursors in FCS. Recent evidence from our study suggests that deficient keratinocyte‐derived growth factors as a possible cause of less than expected repigmentation outcome in FCS. Even though better OCT4 + stem cells and stem cell factor were documented in FCS solution, it was deficient in basic fibroblast growth factor, compared to combined NCES and FCS solution.…”
Section: Cellular Transplantation Methodsmentioning
confidence: 61%
“…In a pilot study, we have documented superior repigmentation of combined NCES and FCS over either NCES or FCS alone in acral vitiligo. Our group (2018) have also demonstrated superior and quicker repigmentation outcome in combined NCES and FCS compared to NCES alone based on a randomized study involving patients with difficult‐to‐treat vitiligo. Apart from better melanocyte growth factors, better OCT4 + stem cells were noted in combined NCES and FCS compared to NCES.…”
Section: Cellular Transplantation Methodsmentioning
confidence: 94%